Validation of the health literacy scale for diabetes as a criterion-referenced test with standard setting procedures. Issue 8 (August 2018) - Kang, Soo Jin; Sim, Kang Hee; Song, Bok Rye; Park, Jeong-Eun; Chang, Soo Jung; Park, Chanho; Lee, Mi Sook
Highlights: Providing skill-based diabetes health literacy measure with psychometric properties. Suggesting scientific cutoff scores method for criterion-referenced assessments based on a standard setting method. Proposing a new approach for establishing performance-based cutoff scores to develop and validate health-related instruments. Abstract: Objective: To develop and examine the psychometric properties of the Korean Health Literacy Scale for Diabetes Mellitus (KHLS-DM), and to establish reasonable cutoff scores. Methods: Initially, 299 items were generated to measure diabetes-related words, numeracy, and information utilization. Content validity assessment and preliminary tests were conducted. After exploratory factor analysis (EFA) and Rasch analysis, the remaining 65 items were administered to a quota sample of 500 diabetic patients aged 40–74 years. The items were narrowed down to 58 items based on an item fit index. To obtain cutoff scores, Jaeger's method and the Bookmark method were employed. Results: A confirmatory factor analysis (CFA) was performed, and a three-factor model was supported (χ 2 /df = 3.891, CFI = 0.92, TLI = 0.91, RMSEA = 0.04). The overall scores ranged from 0 to 58, and two cutoff points were established. The scale exhibited good internal consistency (Cronbach's α = 0.83). Conclusions: The KHLS-DM is a reliable and valid measure with cutoff points to classify individuals into three groups (adequate, marginal, and inadequate). Practice implications: The standard setting may be useful for researchers to validate health literacy measures in other countries and populations.